Comparative Definition of Energy under Public International Organizations - Varis, Ozge (International Journal of Energy Economics and Policy, 2013)
Energy’s significance is accepted by everyone. However, its definition is different for every academic discipline. For scientists, energy is an indirectly observed quantity which is sustained for physical activity. In social sciences, energy has various definitions. Political science energy can be discussed under political authority and power, from the international relations point of view energy is a serious issue for security and nations. Within a legal framework, energy has different definitions for every legal area and legal document. Definitions of energy in legal documents play key roles in politics and international relations. To illustrate the importance of legal definitions, this paper will attempt to define energy under the fundamental regulations of some main international institutions: the United Nations, the Energy Charter Treaty, the World Trade Organization and the International Energy Agency. Keywords: Definition of Energy; International Organizations related with energy JEL Classifications: Q4; K33